Recent Developments in Isoindole Chemistry - Weintraub, Rachel A.; Wang, Xiang (Synthesis, 2022)
Isoindoles are highly reactive aromatic heterocycles that have a variety of important applications in areas such as medicine, analytical detection, and solar energy. Due to their highly reactive nature, isoindoles can be used to access their derivatives, which possess a diverse array of biological activities. However, their reactivity also makes isoindoles unstable and thus, difficult to prepare. Consequently, there has been a need for the development of novel methods that address some of the synthetic challenges and limitations, as well as reactions that utilize isoindoles to access potentially useful compounds. This review will give an overview of the novel reactions reported within the past decade (2012 to 2022) that involve 2H- and 1H-isoindoles and fused isoindoles as reactants, key intermediates, or products. This review is divided into two parts, with the first part focusing on the synthesis of isoindoles and the second part focusing on reactions of isoindoles. The scopes and limitations of the methods described therein will be discussed and the significance of their contributions to the literature will be highlighted. Similar reactions will also be compared.1 Introduction2 Synthesis of Isoindoles2.1 Synthesis of 2H-Isoindoles2.2 Synthesis of 1H-Isoindoles3 Reactions of Isoindoles3.1 Reactions of 2H-Isoindoles3.2 Reactions of 1H-Isoindoles4 Conclusions
Keywords: isoindole; 2H-isoindole; 1H-isoindole; isoindoline; isoindolinone; phthalimide